The ontology of videogames. - Declos, Alexandre (Synthese, 2024)
What are the identity and persistence conditions of videogames? This paper surveys the contemporary philosophical literature on this topic. Specifically, I discuss various views which attempt to ground the identity of videogame works in their rules, in their algorithmic structure, in their source code, or in contextual parameters surrounding gameplay. While these proposals all have merits of their own, I argue that none of them are satisfactory. My conclusion is therefore negative: we still lack an adequate theoretical model to account for the identity and persistence conditions of videogames.